2013
DOI: 10.1111/cas.12100
|View full text |Cite
|
Sign up to set email alerts
|

Low cyclin F expression in hepatocellular carcinoma associates with poor differentiation and unfavorable prognosis

Abstract: Cyclin F, capable of forming Skp1‐Cul1‐F‐box protein ubiquitin ligase complex, is implicated in controlling centrosome duplication and preventing genome instability. Cyclin F oscillates during cell cycle with a similar pattern to cyclin A. However, its expression and significance in cancer remain obscure. In this study, we showed that cyclin F was noticeably decreased in 16 pairs of tissue samples of hepatocellular carcinoma (HCC) compared to paracarcinoma tissues, at both mRNA and protein levels. Immunohistoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 34 publications
0
44
0
Order By: Relevance
“…We therefore propose that the transcriptional suppression mediated by cyclin F serves as an important temporal safeguard maintaining repression of target genes until the p53 response eventually contributes through mechanisms such as the p53-p21-DREAM-CDE/CHR pathway 34,35 . Very interestingly, cyclin F has been shown to be reduced in certain cancer types 36 , whereas B-Myb is overexpressed in several types of cancers 37 . It has been reported that low cyclin F levels correlate with poor differentiation and unfavourable prognosis in hepatocellular carcinoma 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore propose that the transcriptional suppression mediated by cyclin F serves as an important temporal safeguard maintaining repression of target genes until the p53 response eventually contributes through mechanisms such as the p53-p21-DREAM-CDE/CHR pathway 34,35 . Very interestingly, cyclin F has been shown to be reduced in certain cancer types 36 , whereas B-Myb is overexpressed in several types of cancers 37 . It has been reported that low cyclin F levels correlate with poor differentiation and unfavourable prognosis in hepatocellular carcinoma 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Very interestingly, cyclin F has been shown to be reduced in certain cancer types 36 , whereas B-Myb is overexpressed in several types of cancers 37 . It has been reported that low cyclin F levels correlate with poor differentiation and unfavourable prognosis in hepatocellular carcinoma 36 . It is therefore possible that cyclin F plays a relevant role in cancer development by preventing unscheduled cell proliferation and genomic instability through the suppression of B-Myb.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an ideal biomarker should be easily accessible and quantifiable, and procedures for measuring a biomarker should be minimally invasive, inexpensive, accurate, and acceptable to both the patient and the physician. While a variety of proteins and other characteristics associated with a type of cancer including DNA methylation, circulating tumor cells, and histone modifications, have attracted the attention of researchers for early diagnosis and prognosis of HCC, the availability of clinically applicable biomarkers remains limited (Liu et al, 2012;Shen et al, 2012;Fu et al, 2013;Ji et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, the depletion of Fbxo1 in mouse embryonic fibroblasts (MEFs) caused cell cycle defects by an unclear mechanism 59 . Notably, FBXO1 is downregulated in hepatocellular carcinoma, and low expression levels of FBXO1 are associated with larger tumour size, advanced clinical stage, tumour multiplicity and poorer survival, which suggests that FBXO1 could be a promising prognostic marker for hepatocellular carcinoma 60 .…”
Section: Tumour-suppressive F-box Proteinsmentioning
confidence: 99%